2016
DOI: 10.4081/mrm.2016.329
|View full text |Cite
|
Sign up to set email alerts
|

The effect of positive airway pressure therapy on neurocognitive functions, depression and anxiety in obesity hypoventilation syndrome

Abstract: Background: The aim of this study is to evaluate the presence of neurocognitive dysfunctions, depression and anxiety and the effect of positive airway pressure (PAP) therapy on these alterations in Obesity Hypoventilation Syndrome (OHS) patients. Methods: Ten healthy normal and obese controls, 10 OHS and 10 OSAS patients were included in the study. Short form-36, Beck Depression Scale and State-Trade Anxiety Inventory (STAI 1-2) were performed. Wisconsin Card Sorting Test (WCST), Montreal Cognitive Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In line with prior studies, we also found improvements in subjective sleepiness (ESS score), 8,13,[29][30][31]34,36,41,45 depressive symptoms (BDI score), 46 and quality of life (SF-36 score) [29][30][31]36,37,46 at the end of the follow-up period. We have previously reported that in patients with OSA, > 6 h/night of PAP use is associated with a greater improvement in ESS, BDI, and SF-36 scores.…”
Section: Discussionsupporting
confidence: 92%
“…In line with prior studies, we also found improvements in subjective sleepiness (ESS score), 8,13,[29][30][31]34,36,41,45 depressive symptoms (BDI score), 46 and quality of life (SF-36 score) [29][30][31]36,37,46 at the end of the follow-up period. We have previously reported that in patients with OSA, > 6 h/night of PAP use is associated with a greater improvement in ESS, BDI, and SF-36 scores.…”
Section: Discussionsupporting
confidence: 92%
“…3,9,33 In contrast to COPD and interstitial lung disease, there are only a few studies concerning depression in OHS. 16,34 Higher scores on the DEPS questionnaire were associated with greater symptom scores in all ESAS categories in our subjects. Similar results have been reported among patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 55%
“… 3 , 9 , 14 Depressive symptoms increase perceived symptom burden and impair quality of life. 3 , 4 , 15 , 16 They have also been associated with a risk of hospitalization, emergency care use, and impaired prognosis. 14 , 17 , 18 Therefore, systematic screening of depression in patients with advanced respiratory diseases and chronic respiratory insufficiency is warranted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric bypass surgery for morbid obesity not only reduces obesity, but also improves mental health as well (Frezza et al, 2007). Further, decreasing Obesity Hypoventilation Syndrome in those with obesity via positive airway pressure therapy reduces symptoms of anxiety and depression (Argun Baris et al, 2016), again pointing to a reduction in obesity and obesity-related symptoms being related to a reduction in mental distress.…”
Section: Mechanisms Facilitating the Relationship Between Obesity And...mentioning
confidence: 99%